CBCT EVALUATION OF THE AVAILABLE BONE IN THE MAXILLARY PREMOLAR REGION - Sălăvăstru Dan Ionuţ; Nimigean Victor; Cismaş Suzana Carmen; Nimigean Vanda Roxana (Romanian Society of Oral Rehabilitation, 2022)
The maxillary sinus floor is a key anatomical obstacle for implant procedures carried out in the posterior maxilla. The aim of this study was the quantitative and qualitative evaluation of the available bone for dental implant placement in the maxillary premolar region. Material and Methods: Using cone beam computed tomography (CBCT) scans, we analyzed a group of 31 patients, 10 men and 21 women, aged between 40-70 years, who presented edentulous spans in the premolar region of the maxilla. The study was carried out in accordance with the legislation in force. The radiographic measurements were processed in Stata/MP13 software package using Student's t-test, ANOVA test and Kruskal-Wallis test. Results: The average width of the available bone in the region of the maxillary first premolar was 6.44 mm, and in the region of the second premolar it was 7.30 mm. The average height of available bone in the area of the first premolar was 11.78 mm, and in the area of the second premolar it was 11.25 mm. The most common bone density was D3, in 74.19% of cases. Conclusions: The bone density of the maxillary premolar region is lower, and the average dimensions of the available bone are favorable for implant placement in subantral class 1 (SAC 1).